Instrument Development of Self-Confidence for Badminton Athletes - Nyak Amir (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
Standardized measurement with good reliability and validity values to assess levels of selfconfidence of badminton athletes is not yet available in Indonesia. The purpose of this study was to develop such measurement, applicable to the condition of athletes in Indonesia. Subjects (N = 60) were badminton athletes and PBSI coaches in Kabupaten Pidie Aceh Province. The process included two stages: (1) collection of item pool and (2) screening of item pool with Q-sort method. The measurement was then tested on 172 athletes from PBSI Kabupaten Pidie Aceh Province. Data was analyzed through tests for validity, reliability, and factor analysis. Results showed that badminton athlete’s self-confidence measurement consisting of five factors and 38 items is valid and reliable, with index scores of .614 and .872 for validity and reliability respectively.